Towards Implementing The Basic Rules for The Technical Requirements of Cadastral Development in Syria - يحيى منير; زوباري علي; شعبان فادي; حويجه روز (Latakia University Journal -Engineering Sciences Series, 2020)
This research aims to achieve one of the most important technical requirements for cadastral development, It is the spatial concept of the cadastral parcel (Piece of land), and to suggest the basic rules for achieving this. An analytical and design study was conducted, which included cadastral and organizational legislations, cadastral and master plans, the comprehensiveness of the cadastral plan and its relationship to public property. The mechanisms for implementing some organizational and service projects were reviewed. As a result of this research, a modern and comprehensive definition of the spatial concept of the property (as a plot of land) was first presented as one of the most important technical requirements for cadastral development in Syria to include the entire surface of the land, public properties (current cadastral, organizational and divisions streets, public squares ...), in addition to private properties defined Currently, for the purposes of planning and organizing in the municipalities. Secondly, the basic rules were proposed to fulfill this technical requirement; A mechanism was proposed to divide the streets into closed polygons, whose areas are calculated, and each of them is considered a cadastral parcel of a public domain, and a method has been proposed for numbering public parcels with unique numbers within the boundaries of the single cadastral area, and a single identifier number of the property has been developed (public and private domain) ) At the governorate level instead of the cadastral area. Finally, through an analytical study of the design of street plans’ layers, it was found that general cadastral wastes are formed in the areas of implementation of the organization (master plan), and they are restricted to their own layers, numbering, and coding. Recommendations were made regarding the proposal to issue appropriate legislation to define the property in the modern concept and to solve cadastral waste problems.